Interhumanization (Category Art & Design Exhibition) - Mouzouropoulos, Theseas (My University, 2026)
Poster presented at The 3rd International Conference And Exhibition On Semiotics And Visual Communication, Tasos Papadopoulos Building Foyer, Limassol (CYPRUS).